The effect of mountain bike suspensions on vibrations and off-road uphill performance - Faiss, R.; Praz, M.; Meichtry, A.; Gobelet, C.; Deriaz, O. (The Journal of Sports Medicine and Physical Fitness, 2007)
Aim: This study evaluates the effect of front suspension (FS) and dual suspension (DS) mountain-bike on performance and vibrations during off-road uphill riding. Methods: Thirteen male cyclists (27±5 years, 70±6 kg, V.O2max 59±6 mL.kg-1.min-1, mean±SD) performed, in a random sequence, at their lactate threshold, an off-road uphill course (1.69 km, 212 m elevation gain) with both type of bicycles. Variable measured: a) V.O2 consumption (K4b2 analyzer, Cosmed), b) power output (SRM) c) gain in altitude and d) 3-D accelerations under the saddle and at the wheel (Physilog, EPFL, Switzerland). Power spectral analy- sis (Fourier) was performed from the vertical acceleration data. Results: Respectively for the FS and DS mountain bike: speed amounted to 7.5±0.7 km.h-1 and 7.4±0.8 km.h-1, (NS), energy expenditure 1.39±0.16 kW and 1.38±0.18, (NS), gross efficiency 0.161±0.013 and 0.159±0.013, (NS), peak frequency of vibration under the saddle 4.78±2.85 Hz and 2.27±0.2 Hz (P<0.01) and median-frequency of vertical displacements of the saddle 9.41±1.47 Hz and 5.78±2.27 Hz (P<0.01). Conclusion: Vibrations at the saddle level of the DS bike are of low frequencies whereas those of the FS bike are mostly of high frequencies. In the DS bike, the torque produced by the cyclist at the pedal level may generate low frequency vibrations. We conclude that the DS bike absorbs more high frequency vibrations, is more comfortable and performs as well as the FS bicycle.